2011
DOI: 10.1371/journal.pone.0014764
|View full text |Cite
|
Sign up to set email alerts
|

Results of Antiretroviral Treatment Interruption and Intensification in Advanced Multi-Drug Resistant HIV Infection from the OPTIMA Trial

Abstract: BackgroundGuidance is needed on best medical management for advanced HIV disease with multidrug resistance (MDR) and limited retreatment options. We assessed two novel antiretroviral (ARV) treatment approaches in this setting.Methods and FindingsWe conducted a 2×2 factorial randomized open label controlled trial in patients with a CD4 count ≤300 cells/µl who had ARV treatment (ART) failure requiring retreatment, to two options (a) re-treatment with either standard (≤4 ARVs) or intensive (≥5 ARVs) ART and b) ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Participants could change ARVs during the trial as long as they maintained their allocated treatment strategy. No significant differences were found in the primary outcome measure by treatment arm [25].…”
Section: Optima Study Designmentioning
confidence: 74%
See 1 more Smart Citation
“…Participants could change ARVs during the trial as long as they maintained their allocated treatment strategy. No significant differences were found in the primary outcome measure by treatment arm [25].…”
Section: Optima Study Designmentioning
confidence: 74%
“…Participants could change ARVs during the trial as long as they maintained their allocated treatment strategy. No significant differences were found in the primary outcome measure by treatment arm [25].For the purpose of this substudy, we combined the subgroups receiving standard and mega-ARV regimens within the ARDFP and the no-ARDFP groups. Viral RC and phenotypic drug susceptibility were retrospectively tested on frozen, stored (-70 o C) ethylenediaminetetraacetic acid (EDTA) plasma samples collected from OPTIMA participants enrolled at Veterans Administration (VA) hospitals.…”
mentioning
confidence: 99%
“…We assumed that discontinuation of older drugs was not associated with worse virologic outcomes, since randomized trials have demonstrated no benefit from continuing multiple conventional antiretroviral drugs. 4, 27 We assumed that new regimens might contain some older drugs for two reasons. First, they might have residual antiretroviral activity.…”
Section: Methodsmentioning
confidence: 99%
“…4 We estimated parameters that were not available within OPTIMA from the literature (Supplementary Digital Content 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation